A third generation regimen VACOP-B with or without adjuvant radiotherapy for aggressive localized non-Hodgkin's lymphoma: report from the Italian Non-Hodgkin's Lymphoma Co-operative Study Group - G. Santini; C. De Souza; S. Aversa; C. Patti; L. Tedeschi; M. Candela; A. Olivieri; T. Chisesi; A. Rubagotti; R. Centurioni; V. Nardi; M. Congiu; et al. (Brazilian Journal of Medical and Biological Research, 2004)
The objective of this multicenter prospective study was to determine the clinical efficacy and toxicity of a polychemotherapeutic third generation regimen, VACOP-B, with or without radiotherapy as front-line therapy in aggressive localized non-Hodgkin's lymphoma. Ninety-three adult patients (47 males and 46 females, median age 45 years) with aggressive localized non-Hodgkin's lymphoma, 43 in stage I and 50 in stage II (non-bulky), were included in the study. Stage I patients received VACOP-B for 6 weeks plus involved field radiotherapy and stage II patients received 12 weeks VACOP-B plus involved field radiotherapy on residual masses. Eighty-six (92.5%) achieved complete remission and 4 (4.3%) partial remission. Three patients (3.2%) were primarily resistant. Ten-year probability of survival, progression-free survival and disease-free survival were 87.3, 79.9 and 83.9%, respectively. Eighty-four patients are surviving at a median observation time of 57 months (range: 6-126). Statistical analysis showed no difference between stages I and II in terms of response, ten-year probability of survival, progression-free survival or disease-free survival. Side effects and toxicity were negligible and were similar in the two patient groups. The results of this prospective study suggest that 6 weeks of VACOP-B treatment plus radiotherapy may be the therapy of choice in stage I aggressive non-Hodgkin's lymphoma. Twelve weeks of VACOP-B treatment with or without radiotherapy was shown to be effective and feasible for stage II. These observations need to be confirmed by a phase III study comparing first and third generation protocols in stage I-II aggressive non-Hodgkin's lymphoma.